Potential Implementation of Economic Waqf in the State of Kelantan: A Preliminary Survey - Mujiburrahman Muhammad Saleh; Nurul Akma Mohamed; Hamidi Abdul Ghani; Suraini Saufi (Rabbanica: Journal of Revealed Knowledge)
The Islamic social finance sector, including waqf, is growing rapidly but is still too small compared to its true potential and has yet to be fully explored. One of the main reasons that hinders this growth is the lack of innovation in the management of waqf property to work on the real potential of the property to provide optimal impact to the economy of the ummah. In the context of Kelantan state, Islamic educational institutions have succeeded in producing a society that understands religious knowledge well. This is the principal capital for aggressively developing waqf instruments in Kelantan with innovations. This paper discusses the concept of economic endowment and the potential of its implementation in the state of Kelantan. This qualitative study is done descriptively by utilising content analysis methods in the analysis process. By looking at the existing concept used by several waqf administrative institutions in Malaysia, this study found that the state of Kelantan has excellent potential to develop economic waqf, namely the idea of waqf that benefits from waqf assets used for economic development in business, agriculture, and other sectors.